The Impact of Intuitive Eating on Physical Appearance Comparison Among Working Women.. - Nisa, Fakhr Un; Faiz, Aasia; Kashif, Muhammad; Ali Khan Jafri, Mahmood; Ali Shah, Syed Mahboob (Journal of Neonatal Surgery, 2025)
Background: the relationship between intuitive eating and physical appearance comparison among working women. It explores how intuitive eating impacts self-perception, body image, and emotional well-being in a demographic affected by societal beauty standards. Objectives: To explore the relationship between intuitive eating and physical appearance comparison in working women and assess the impact of exercise, fitness goals, profession, and job experience on these variables. Study Design: a cross sectional study. Place and Durtion of Study. Department of Psychiatry Rawalpindi Medical University Rawalpindi, Pakistan from jan 2024 to june 2024 Methods: The Intuitive Eating Scale-2 (Tylka, 2006) and the Physical Appearance Comparison Revised Scale (Schaefer and Thompson, 2014) were administered to 150 working women in Rawalpindi to establish a cross-sectional study. The data was subjected to analysis with SPSS regression analysis and correlation analysis. Results:the Mean age was 32.6 years with a standard deviation of 5.4 years. The correlation between intuitive eating and physical appearance comparison was significant (p < 0.01) indicating that greater levels of intuitive eating diminish the desire to compare physical appearance among working women. Conclusion: Encouraging introspective eating in working women may help boost their body image satisfaction and diminish effects of physical appearance comparison and thereby achieve improved emotional well-being and enhanced performance in the workplace..